Variable phenotypic expression including late presentation of hypertrophic cardiomyopathy in LEOPARD syndrome with P.Q510E mutation in PTPN11 gene - Sayeed, Md. Zahidus; Salam, Md. Abdus; Siddiqui, Muhammad Afsar; Chandra, Pampa; Bhaduri, Joydeep; Bhuiyan, Zahurul A (2015)
LEOPARD syndrome is a complex dysmorphogenetic disorder of variable penetrance and expressivity. Mutations in the PTPN11 gene are frequently reported in patients with Noonan syndrome (NS) and LEOPARD syndrome (LS). Q510E mutation in PTPN11 has always been associated with lethal or rapidly progressive hypertrophic cardiomyopathy both in NS and LS patients. Besides, deafness is also frequently present in these patients, but reproductive fitness is questioned. We herein describe a case of LEOPARD syndrome from Bangladesh with Q510E mutation in the PTPN11 gene. Our patient almost fulfilled the entire acronym of LEOPARD with very late presentation of hypertrophic cardiomyopathy at the age of 36 yrs. Interestingly patient has intact hearing and normal reproductive capacity, biologically fathered two children.